Optomechatronics (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
The field of optomechatronics provides synergistic effects of optics, mechanics and electronics for efficient sensor development. Optical sensors for the measurement of mechanical quantities, equipped with appropriate electronic signal (pre)processing means have a wide range of applications, from surface testing, stress monitoring, thin film analysis to biochemical sensing. The aim of this special issue is to provide an overview of actual research and innovative applications of optomechatronics in sensors. Papers addressing, inter alia, optical sensor principles, fiber-optic sensors, electronic speckle pattern interferometry, surface analysis, thin film measurement, FGB sensors, and biochemical sensors are provided.